Evolution of religion in memetics (Dawkins, Dennett) - Rusek, Damian (Hybris, 2015)
Since ‘The Selfish Gene’ by Richard Dawkins was published the notion of evolving culture has become a matter of a growing concern which appears to be especially intriguing from the perspective of biology (R. Dawkins), psychology (R. Brodie) as well as philosophy (D. Dennett). The essence of Darwin’s project is a natural selection within the sphere of a natural science. From this standpoint, a human is considered to be an effect of an evolutionary development. In the memetics approach, a human being is perceived in a different manner. An unit of gene, which task is to pass on the information in a process of a natural selection, has been replaced by a notion of a meme that is an entirely new replicator which, as opposed to a gene, may be applied to the various environments, not only a biological one. The crucial factor that determines the uniqueness of every man would be culture. From this point of view, the transfer of culture, which is developing in a specific procedure, is emphasized. What can be included in the evolutionary processes in the vast area of culture? What is the discrepancy between the Dawkins’s biological position and the grounded on a philosophy of mind the position of Dennett? The above mentioned attitudes result in various definitions of meme as well as the further implications that result from these definitions. Does the Theory of Cultural Selection fully explain a matter of the origin and evolution of languages, societies and religions?